Antianginal treatment of stable angina: focus on heart rate reduction - Yu. M. Lopatin (Кардиоваскулярная терапия и профилактика)
The article is focused on modern approaches to heart rate reduction, as a new method for stable angina (SA) management. The algorhithm of SA pharmaceutical treatment, by the European Society of Cardiology (2006), is analyzed.